Method Matters : Underreporting of Intimate Partner Violence in Nigeria and Rwanda - Cullen, Claire (World Bank, Washington, DC, 2020)
This paper analyzes the magnitude and predictors of misreporting on intimate partner and sexual violence in Nigeria and Rwanda. Respondents were randomly assigned to answer questions using one of three survey methods: an indirect method (list experiment) that gives respondents anonymity; a direct, self-administered method that increases privacy; and the standard, direct face-to-face method. In Rwanda, intimate partner violence rates increase by 100 percent, and in Nigeria, they increase by up to 39 percent when measured using the list method, compared with direct methods. Misreporting was associated with indicators often targeted in women's empowerment programs, such as gender norms and female employment and education. These results suggest that standard survey methods may generate significant underestimates of the prevalence of intimate partner violence and biased correlations and treatment effect estimates.